Complex Event Processing (CEP) - Using SQL Server StreamInsight for Near Real-Time Visualization and Monitoring - Rolando Emanuel Lopes Pereira (2013)
Nowadays business needs to react in real time to events that happen during their work. These events appear as streams of events, where each event has occurred during a point in time.A popular way to process those event streams, is by using Complex Event Processing. This technology allows the processing, in real time, of event streams, the creating of time windows over those streams and the use of aggregations on those windows. Usually this functionality is gained by using a CEP engine that extends the SQL language allowing the latter to process streams by constructing queries and create temporal windows on them.Unfortunately before using a CEP system, many require à priori knowledge regarding the type (i.e. schema) of events that can appear on their streams and what queries it can run. This dissertation implements a CEP system that can work without knowing the type of events that may appear, but still has the ability to create queries over those event.The CEP engine used in this dissertation was Microsoft's StreamInsight.